A teoria da actio libera in causa e a imputabilidade penal - Bittencourt, Ila Barbosa (2006)
Since the beginning of civilization there has been alcoholic use just for simple pleasure or for stimulation. But device excessive alcoholic beverage or another substances of similar effects use has been increased the number of social and health problems, and then, has became an society object of study, From Health point of view, alcoholism is a chronic, progressive, and fatal disease, which has physical and psychological effects. Particularly and as object of study of this paper, there is yet the judiciary point of view about drunkenness and its effects throw the decades. Our penal system does not punish the act of drinking and declare free of punishment the individual that who at the moment of the act do not have the capacity of understand the unlawfulness of his act or to behave in accordance with this understanding. For long time in our Penal Code, drunkenness was considered an attenuate for crimes committed under its effect device the agent partial or complete privation of senses, fact which will be approached in this one, besides the comparison of other countries legislation treatment for this subject. Nowadays, voluntary or culpable drunkenness does not exclude imputability, unless in cases it is result from accident or majored force. And if the individual has intentionally drunk for practice a crime, or to lose partial or completely conscience, or gain courage, or to try to use this fact as an attenuating excuse, otherwise, it will work as an aggravator. In these cases of partial or complete mental privation enters the institute of actione liberae in causa, which consist in a criminal politic of penal responsabilization that assumes the produced result in unimputability stage should be estimated or wanted by the agent, and this one had been put himself in this situation for practicing the crime or to have an excuse for it. Among the doctrinaire divergences approached in this work, deserves a different position the confusion of action libera in causa and the objective responsibility. But in the fist one is necessary to be present intention or guiltiness, or in other words a psychological nexus, in a antecedent moment related to the crime